2010
DOI: 10.3390/ma3042567
|View full text |Cite
|
Sign up to set email alerts
|

Novel Materials through Non-Hydrolytic Sol-Gel Processing: Negative Thermal Expansion Oxides and Beyond

Abstract: Low temperature methods have been applied to the synthesis of many advanced materials. Non-hydrolytic sol-gel (NHSG) processes offer an elegant route to stable and metastable phases at low temperatures. Excellent atomic level homogeneity gives access to polymorphs that are difficult or impossible to obtain by other methods. The NHSG approach is most commonly applied to the preparation of metal oxides, but can be easily extended to metal sulfides. Exploration of experimental variables allows control over produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 122 publications
(169 reference statements)
0
20
0
1
Order By: Relevance
“…One of their research topics is the synthesis of crystalline ternary and quaternary metal oxides with A 2 M 3 O 12 stoichiometry (A = Al, Sc, Fe, In, Ga, Y, Mg-Zr, Mg-Hf, etc. ; M = Mo or W) that exhibit negative thermal expansion (NTE) [62][63][64][65]188,189]. The intrinsic advantage of NHSG chemistry-a high homogeneity of element mixing was fully exploited for NTE materials preparation.…”
Section: New Compositionsmentioning
confidence: 99%
“…One of their research topics is the synthesis of crystalline ternary and quaternary metal oxides with A 2 M 3 O 12 stoichiometry (A = Al, Sc, Fe, In, Ga, Y, Mg-Zr, Mg-Hf, etc. ; M = Mo or W) that exhibit negative thermal expansion (NTE) [62][63][64][65]188,189]. The intrinsic advantage of NHSG chemistry-a high homogeneity of element mixing was fully exploited for NTE materials preparation.…”
Section: New Compositionsmentioning
confidence: 99%
“…One such method is the non-hydrolytic sol gel (NHSG) process, which was shown to provide an elegant route to mixed metal oxides [60,61,62,63,64]. It was previously demonstrated that this chemistry can be applied to the synthesis of A 2 M 3 O 12 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the NHSG route features different reactions and reaction conditions, which significantly affect the texture, homogeneity and surface chemistry of the resulting oxide [4][5][6]. In the past 20 years, several non-hydrolytic synthesis methods of oxides and mixed oxides have been described, involving the reaction of precursors (alkoxides, chlorides, acetylacetonates) with oxygen donors (ethers, alcohols, ketones) [4][5][6][7][8][9][10]. The main non-hydrolytic routes involve the reaction of a metal chloride with either a metal alkoxide or organic ether, acting as oxygen donors [7][8][9] as described in Figure 1.…”
mentioning
confidence: 99%
“…In the past 20 years, several non-hydrolytic synthesis methods of oxides and mixed oxides have been described, involving the reaction of precursors (alkoxides, chlorides, acetylacetonates) with oxygen donors (ethers, alcohols, ketones) [4][5][6][7][8][9][10]. The main non-hydrolytic routes involve the reaction of a metal chloride with either a metal alkoxide or organic ether, acting as oxygen donors [7][8][9] as described in Figure 1. On the other hand, the formation of alkyl halide and/or alkyl ethers as by-products and the potential incompatibility with oxygen containing species have to be taken into account as possible negative aspects.…”
mentioning
confidence: 99%